THE IMPORTANT ROLES OF BEING A SECRETARY ASSISTANT IN YOGYAKARTA CITY CULTURE OFFICE - A. Muhammad Taufiq Rahman, 151411813072 (2018)
From discussions, obstacles, and added values that were included in the previous chapter of this report, the writer then got some conclusions. First, during the internship, the writer learned how to archive the files at Yogyakarta City Culture Office. The writer was given the responsibility to archive the files of the institution besides the correspondence job. His archiving responsibility was proven to be difficult as the writer did not have any experience regarding how to archive swiftly and without any mistake. The writer had to learn from zero in archiving the files of the institution. Besides that, he also asked his fellow secretary and his supervisor how to do the archiving job quicker and smarter. It was revealed that in order to ease the difficulty in archiving files, the writer was told to follow the files codes. There are many different kinds of codes that separate one filefrom another. All the writer had to do was separate the files and put them where they belong according to the code of each file. knowing the file coding really helped the writer because before he knew about it, the writer was overwhelmed and confused by the responsibility of archiving that files. The second conclusion that the writer got is regarding correspondence at Yogyakarta City Culture Office. At first, the writer was unable to make so many letters without any guidance from the institution. Eventually, the institution, Yogyakarta City Culture Office, gave the writer templates for each kind of letter to improve the quality of the letter that would be sent to other parties. Those templates are useful for improving the qualities of letters made by Yogyakarta City Culture Office. These templates are important to set the standard of letters made by the institution that can be useful in maintaining the reputation and credibility of Yogyakarta City Culture Office as the representation of Indonesian Government in the sector of Yogyakarta’s tourism. Lastly, The internship that the writer did at Yogyakarta City Culture Office has given him so many benefits and values. There are practically many things obtained that can be useful in the future after doing the internship at the institution.